Comparative effects of aerobic dance and jogging on the resting heart rate and body mass index of junior secondary school teachers - Nwadibia, Glory Anwuri; Mong, Emeka Usman; Gonsi, Monday Sibe; Ekpo, Geraldine Umoh Amba (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study examined the effects of aerobic dance and jogging on the resting heart rate and body mass index of junior secondary school teachers in Ogba-Egbema-Ndoni Local Government Area (ONELGA). The study adopted an experimental design with a sample size of thirty (30) teachers, who were randomly selected from six junior secondary schools in ONELGA. The participants were randomly allocated into three groups, each consisting of ten (10) teachers: the control group and two experimental groups. They were also subjected to a 30-minute session of aerobic dance and jogging, and their physiological characteristics were evaluated. The finding was that the resting heart rate recorded a mean difference of 7.35, 7, and 10.9, while the mean gains were 3.55 and 3.9, respectively. The body mass index recorded the mean difference as 1.13, 0.962, and 0.54, while the mean gain was 0.59 and 0.422, respectively. This implies that aerobic dance and jogging affect the resting heart rate and body mass index of junior secondary school teachers in ONELGA. Therefore, it is recommended that junior secondary school teachers in ONELGA incorporate aerobic dance and jogging into their daily routine as a means to enhance the functioning of their RHR and BMI.